2014
DOI: 10.4025/cienccuidsaude.v13i3.20341
|View full text |Cite
|
Sign up to set email alerts
|

<b>Auriculoterapia: tratamento dos transtornos da amamentação</b> DOI:10.4025/cienccuidsaude.v13i3.20341

Abstract: RESUMO O leite materno possui inúmeros benefícios para mãe e para o filho. No Brasil, as crianças têm mamado apenas até os 11 meses, sendo depois excluída totalmente essa oferta. Este valor está bem abaixo da recomendação da Organização Mundial de Saúde (OMS) que é até os 24 meses. Os fatores para o abandono mais citados são a dor e o ingurgitamento mamário. A propósito disso, a auriculoterapia constitui um tratamento para enfermidades físicas e mentais, através de estímulo de pontos do pavilhão auricular. Est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Unlike our study, researchers in an earlier study examining the effectiveness of auricular acupressure on breast pain among participants who delivered by Cesarean section (Lee et al, 2010) found auricular acupuncture to be strongly associated with subjective pain relief. In a case series, researchers reported an 85.7% subjective pain reduction among participants who were experiencing pain during breastfeeding after applying auricular acupressure (Maymone et al, 2014). While there are very few studies investigating auricular acupressure’s effectiveness during breastfeeding, some studies have explored its application in breast cancer patients with breast pain (Chien et al, 2015; Vallim et al, 2019), and participants experiencing menstrual-related breast pain ( L.Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike our study, researchers in an earlier study examining the effectiveness of auricular acupressure on breast pain among participants who delivered by Cesarean section (Lee et al, 2010) found auricular acupuncture to be strongly associated with subjective pain relief. In a case series, researchers reported an 85.7% subjective pain reduction among participants who were experiencing pain during breastfeeding after applying auricular acupressure (Maymone et al, 2014). While there are very few studies investigating auricular acupressure’s effectiveness during breastfeeding, some studies have explored its application in breast cancer patients with breast pain (Chien et al, 2015; Vallim et al, 2019), and participants experiencing menstrual-related breast pain ( L.Li et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to a study that applied auricular acupressure and auricular acupuncture to breastfeeding participants, breast pain significantly decreased after applying auricular acupuncture; however, the research was a case study that used only objective indicators from seven breastfeeding mothers without a control group, and the placebo effect could not be identified (Maymone et al, 2014). Today, studies that examine the effects of auricular acupressure on pain improvement in various diseases are being actively conducted (Yang et al, 2020; You et al, 2019), but there are insufficient studies that identify the effect of auricular acupressure on breast pain in breastfeeding parents who also receive gentle and standardized breast massage in relation to breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…Com o objetivo de analisar os efeitos da acupuntura auricular nas complicações da lactação um estudo identificou que mães que receberam a intervenção apresentaram melhoras nos aspectos relacionados a dor, redução da inflamação, tempo de tratamento, tempo de cicatrização e apojadura (MAYMONE et al, 2014).…”
Section: Acupuntura Auricular E Aleitamento Maternounclassified